Arctic coastal dynamics of Eurasia – results of two ACD-related INTAS projects : extended abstract - Rachold, Volker; Cherkashov, Georgy; Grigoriev, Mikhail N.; Ødegård, R. S.; Ostroumov, V. E.; Pavlidis, Y. A.; Nikiforov, S. L.; Rivkin, F. M.; Sollid, J. L.; Etzelmüller, B.; Streletskaya, I. D.; Vasiliev, A. A.; et al. (AWI, Alfred-Wegener-Institut für Polar- und Meeresforschung, 2005)
Under the framework of the Arctic Coastal Dynamics (ACD) program two projects of the International Association for the Promotion of Co-operation with Scientists from the New Independent States of the Former Soviet Union (INTAS) focused on ACD related topics. The objectives of the first project "Arctic coastal dynamics of Eurasia: classification, modern state and prediction of its development based on GIS technology" (2002-2004) had been to develop a coastal classification and to generate GIS based map products for the coastal Zone of the Eurasian Arctic. The Russian Part of the circum-Arctic ACD classification and segmentation has been completed within this project. The overall objective of the second project "Arctic coasts of Eurasia: dynamics, sediment budget and carbon flux in connection with permafrost degradation" (2002-2005) is to quantify the material flux through coastal erosion in order to improve our understanding of the Arctic sediment and organic carbon budget. This presentation summarizes the main results of the two projects and provides an overview of more specific results which are shown in a series of Posters.